Screening and Functional Pathway Analysis of Pulmonary Genes Associated with Suppression of Allergic Airway Inflammation by Adipose Stem Cell-Derived Extracellular Vesicles. (27th June 2020) - Kim, Sung-Dong; Kang, Shin Ae; Kim, Yong-Wan; Yu, Hak Sun; Cho, Kyu-Sup; Roh, Hwan-Jung
Abstract : Background . Although mesenchymal stem cell- (MSC-) derived extracellular vesicles (EVs) are as effective as MSCs in the suppression of allergic airway inflammation, few studies have explored the molecular mechanisms of MSC-derived EVs in allergic airway diseases. The objective of this study was to evaluate differentially expressed genes (DEGs) in the lung associated with the suppression of allergic airway inflammation using adipose stem cell- (ASC-) derived EVs. Methods . C57BL/6 mice were sensitized to ovalbumin (OVA) by intraperitoneal injection and challenged intranasally with OVA. To evaluate the effect of ASC-derived EVs on allergic airway inflammation, 10 μ g/50 μ L of EVs were administered intranasally prior to OVA challenge. Lung tissues were removed and DEGs were compared pairwise among the three groups. DEG profiles and hierarchical clustering of the identified genes were analyzed to evaluate changes in gene expression. Real-time PCR was performed to determine the expression levels of genes upregulated after treatment with ASC-derived EVs. Enrichment analysis based on the Gene Ontology (GO) database and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were also performed to further identify the function of DEGs. Results . Expression of paraoxonase 1 (PON1), brain-expressed X-linked 2 (Bex2), insulin-like growth factor binding protein 6 (Igfbp6), formyl peptide receptor 1 (Fpr1), and secretoglobin family 1C member 1 (Scgb1c1) was significantly increased in asthmatic mice following treatment with ASC-derived EVs. GO enrichment and KEGG pathway analysis showed that these genes were strongly associated with immune system processes and their regulation, cellular processes, single-organism processes, and biological regulation. Conclusion . These results suggest that the DEGs identified in this study (PON1, Bex2, Igfbp6, Fpr1, and Scgb1c1) may be involved in the amelioration of allergic airway inflammation by ASC-derived EVs.